Corporate taxation and its reform:the effects on corporate financing decisions in Italy - Maria Elena Bontempi; Silvia Giannini; Roberto Golinelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
The aim of this paper is twofold. First, we measure the relationship between fiscal variables and companies debt choices in Italy using a dynamic representation of the modified pecking order model, where both trade-off and pecking order theories are nested. Second, our estimation results are used, jointly with some tax simulations undertaken with a company microsimulation tax-model (MATÍS), to assess the effects on leverage of two recent tax reforms in Italy since 1996. Main results suggest that: (a) fiscal effects are significant and robust explanations of firms' financial behaviour; (b) the reforms analysed are able to induce similar reductions in firms' leverage, when compared with the situation prevailing in 1996. However, the routes through which this occurs are different (relative price in the first case, cash flow in the second), tracing some important differences in the overall evaluation of the two reforms.
Keywords: 330; Unternehmensbesteuerung; Steuerreform; Steuerwirkung; Unternehmensfinanzierung; Kapitalstruktur; Simulation; Italien